THE RADIOACTIVITY ANALYSIS IN AP1000 CORE AND PRIMARY COOLANT SYSTEM - ROHANDA (NIM : 20210019); Pembimbing : Dr. Eng. Abdul Waris, ANIS
The Radioactivity Analysis in AP1000 Core and Primary Coolant System. The radioactivity information plays important role in radiation safety calculation and for reactor operational. Radiation strength (radiation source) and radioisotopes concentration are the important radioactivity information should be known. Thus study is needed and it performs to determine gamma strength in core and the concentration of radioisotopes in reactor coolant (primary coolant). The analysis was performed on the configuration basis and operational of Westinghouse AP1000 power reactor using ORIGEN2.1. In gamma source analysis (MeV/watt-s), analysis was performed in first cycle core in 18 gamma energy groups at various cooling time after shut down. The analysis of radioisotopes concentrations ((mu)Ci/gram) was performed with assumed that 0,25% radioisotopes are release from cladding to reactor coolant. By using analytical methode based on activation and redecay princip, the N-16 analysis as predominant contributor to the activity in the reactor coolant system during reactor operation was also performed. The results of analysis with ORIGEN2.1 and analytical methode are compared with AP1000 design control document as standard values. The comparison results in source gamma analysis shows the good result in several gamma energy groups and in general, the value will decreases as a function of cooling time. The smallest deviation, 2,18% is found in 0,300-0,450 MeV gamma energy group with 1 week cooling time. In general, the obtained results showed that the radioisotopes concentration in the reactor coolant using ORIGEN2.1 more lower than AP1000 standard. Smallest deviations are found in Xe-138 isotope at 3,84%. The results of the calculation of N-16 concentration at the core outlet, reactor vessel outlet, pressurizer line, inlet and outlet of steam generators, primary pumps, reactor vessels inlet and core inlet are: 281, 257, 255, 250, 145, 142, 129 and 112 (mu)Ci/gram respectively. The results of analysis compared with AP1000 design control document as standard values. The verification showed very high accuracy comparation between analytical results and standard values.